Analysis of the Increase in Efficacy and Motivation to Learn Mathematics towards the Use of Interactive Learning Model in Elementary School - Aini, Qurrota; Aisyah, Diah Nur; Putri, Tasya Intania; Supriyadi, Supriyadi; Izzatika, Amrina (Indonesian Journal of Education and Mathematical Science, 2024)
Learning mathematics is very important as a guide in problem solving, logical reasoning in everyday life. In increasing the desire of students in the field of mathematics, which in most students' views is learning that is difficult to understand and scary. so that an innovation is needed along with the times of science and technology in the form of using interactive learning models with the help of media according to the existing material. the use of interactive learning models can foster self-efficacy and motivation in students so that they are able to implement mathematics in solving problems in everyday life.